Media Matters, Examining Historical and Modern Streptococcus pneumoniae Growth Media and the Experiments They Affect - Sanchez-Rosario, Yamil; Johnson, Michael D. L. (Frontiers in Cellular and Infection Microbiology, 2021)
While some bacteria can thrive for generations in minerals and salts, many require lavish nutrition and specific chemicals to survive to the point where they can be observed and researched. Although researchers once boiled and rendered animal flesh and bones to obtain a media that facilitated bacterial growth, we now have a plethora of formulations and manufacturers to provide dehydrated flavors of historical, modified, and modern media. The purpose of media has evolved from simple isolation to more measured study. However, in some instances, media formulated to aid the metabolic, nutritional, or physical properties of microbes may not be best suited for studying pathogen behavior or resilience as a function of host interactions. While there have been comparative studies on handfuls of these media in Streptococcus pneumoniae, this review focuses on describing both the historical and modern composition of common complex (Todd Hewitt and M17), semi-defined (Adams and Roe), and defined pneumococcal media (RPMI and Van de Rijn and Kessler), key components discovered/needed for cultivation/growth enhancement, and effects these different media have on bacterial phenotypes and experimental outcomes. While many researchers find the best conditions to grow and experiment on their bacteria of choice, the reasons for some researchers to use a specific medium is at best, not discussed, and at worst, arbitrary. As such, the goal of this review is to highlight the differences in pneumococcal media to encourage investigators to challenge their decisions on why they use a given medium, discuss the recipe, and explain their reasoning.